Revisiting the controversy: The role of fungi in chronic rhinosinusitis. Issue 11 (2nd June 2021) - Tyler, Matthew A.; Lam, Kent; Marino, Michael J.; Yao, William C.; Schmale, Isaac; Citardi, Martin J.; Luong, Amber U.
Abstract: In the last two decades, the development of culture‐independent genomic techniques has facilitated an increased appreciation of the microbiota‐immunity interactions and their role in a multitude of chronic inflammatory diseases such as chronic rhinosinusitis (CRS), asthma, inflammatory bowel disease and dermatitis. While the pathologic role of bacteria in chronic inflammatory diseases is generally accepted, the understanding of the role of fungi remains controversial. Chronic rhinosinusitis, specifically the phenotype linked to nasal polyps, represents a spectrum of chronic inflammatory diseases typically characterized by a type 2 immune response. Studies on the microbiota within sinus cavities from healthy and diseased patients have focused on the bacterial community, mainly highlighting the loss of diversity associated with sinus inflammation. Within the various CRS with nasal polyps (CRSwNP) phenotypes, allergic fungal rhinosinusitis presents an opportunity to investigate the role of fungi in chronic type 2 immune responses as well as the antifungal immune pathways designed to prevent invasive fungal diseases. In this review, we examine the spectrum of fungi‐associated sinus diseases highlighting the interaction between fungal species and host immune status on disease presentation. With a focus on fungi and type 2 immune response, we highlight the current knowledge and its limitations of the sinus mycobiota along with cellular interactions and activated molecular pathways linked to fungi.